Социально-психологический подход к проблемам теории познания - Юрова, Ирина; Yurova, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статье анализируется социально-психологический подход к гносеологической проблематике, а именно проблема перцепции и формирование суждения в условиях неопределенности. The author of the article analyzes the socio-psychological approach to the epistemological problems, in particular perception and forming of judgment under condition of uncertainty. Special importance is attached to value aspect of the formation of judgments that is influenced by cultural and personal contexts. The author investigates the conception of B. A. Yerunov, who considered forming of judgment to come from perception. Perhaps, he was sure that such view is not the way to agnosticism, because socio-psychological approach must not only overcome agnosticism and subjectivism, it helps to find the answer to “What knowledge is”.
Socio-Psychological Approach to the Problems of the Theory of Knowledge
Keywords: перцепция; perception; неопределенность; uncertainty; теория познания; theory of knowledge; теория суждения; theory ofjudgment; социально-психологическтй подход; socio-psychological approach